Associating Importance with Behavior: Providing Direction for Water Conservation Communication - Alexa J. Lamm; Lisa K. Lundy; Laura Warner; Kevan W. Lamm (Journal of Applied Communications, 2016)
This study identified differences in characteristics of High Water Users (HWUs) based on their perceived importance of plentiful water and their engagement in water conservation behaviors. Differences in the characteristics of high water users based on the level of importance they associated with plentiful water and their engagement in water conservation behaviors were identified. Communication needs and interests of HWUs were also identified. The Situational Theory of Publics (STP) was applied to explore why HWUs might perceive plentiful water to be important but may not feel personally responsible and may perceive barriers to changing their behaviors. Significant differences were found in terms of gender and race between the four primary groups of respondents identified (High Importance/High Engagement, Low Importance/High Engagement, Low Importance/Low Engagement and High Importance/Low Engagement). The High Importance/Low Engagement group was identified as an important and potentially high impact public for communicators.
Keywords: Segmenting Publics; Situational Theory of Publics; Water Conservation